Coelomic foreign bodies in wild-caught Python spp. in the Greater Everglades Ecosystem, Florida, USA - Gretchen E. Anderson; McKayla M. Spencer; Ray W. Snow; Andrea F. Currylow; Frank N. Ridgley; Bryan G. Falk; Amy A. Yackel Adams (NeoBiota)
Burmese pythons (Python molurus bivittatus) and African rock pythons (Python sebae) have established invasive populations in southern Florida, severely disrupting local ecosystems. We analysed necropsy data from 2,179 pythons captured between 2006 and 2022, revealing nine cases of coelomic foreign bodies, primarily consisting of bird beaks, which presumably entered the coelom following gastrointestinal perforations during prey consumption. Despite the presence of foreign bodies, most examined pythons exhibited no obvious health issues. These findings indicate that the consumption of prey with sharp morphological features, such as wading birds, may not impede the pythons’ survival or health significantly, thereby underscoring their adaptability as apex predators in the Greater Everglades Ecosystem.